Pirolisis Kulit Kayu Pinus (Merkusii) Menjadi Bio-Oil Dengan Katalis Mo/NZA - Yuliati Eka Putri; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Global issues becoming a serious discussion in the depletion of oil reserves and coal. Dependence at fuel on nonrenewable energy sources should be avoided, sooner or later energy sources will run out. We have to look for other sources of energy that can be updated to cope of with these problems. One of the alternative energy that can be developed bio-oil. Bio-oil is produced with the use of biomass by pyrolysis process. The purpose of this research is to determine the effect of Mo metal on the catalyst Mo / NZA as well as influence of the catalyst on the bio-oil produced. Physical properties such as density, viscosity, acidity and a flash point of bio-oil were measured. And the chemical components of the bio-oil measured by GC-MS method. Pyrolysis using pine bark as much as 50 grams along with 500 ml silinap with variations Mo metal to NZA 0%; 0,5%; 1% and 1,5% w / w and the weight variation of the catalyst Mo/NZA 3%, 6% and 9% of the biomass. The process having stirring speed of 300 rpm and temperature of 320ºC for 120 min. The Highest yield of bio-oil obtained of 1,5% catalyst Mo/NZA with 9% of the amount of catalyst was 67,16%. From physical analysis conducted on bio-oil were obtained: density 0,781 g/ml, viscosity 2,094 cSt, acidity 20,906 mg NaOH/g sample, and the flash point 52 oC respectively. From the GC-MS analysis, the dominant chemical components at bio-oil is a 1-Propene (12,19%), 2-Pentene (8,2%), Pentane (10,54%), Cyclohexane (13,78%) and Heptane (3,52%) respectively.Keywords : Bio-oil, Mo/NZA, Pine bark, Pyrolysis